PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI MODEL PROBLEM BASED LEARNING DENGAN MEDIA AUDIOVISUAL (Universitas Negeri Semarang, 2016)
The purpose of research was to improve the instructional quality of IPA (Natural Sciences) learning through Problem-based Learning (PBL) model by using audio-visual media for fifth graders of SDN Tambakaji 05 Semarang. This research design was classroom action research consisted of three cycles with four stages, namely: planning, implementing, observating, and reflection. The collecting data used test, observation, documentation, and field notes. The data were analyze using quantitative and qualitative descriptive analyze. The result showed that: (1) the teacher’s skill in the cycle I gained score 17 (good), 19 in the cycle II (very good), 22 in the cycle III (very good) ; (2) the score of students activity in the cycle I was 12.76 (good), 14.53 in the cycle II (good), 17.53 in the cycle III (good); 3) then, the learning outcome was 48.78 % in the cycle I, 68.29 % in the cycle II, and 82.93 % in the cycle III. Therefore, it can be concluded that PBL model with audio-visual media can improve the quality of natural sciences.